Silvicultural Efficiency of the Thinning Efficiency of Pinus sylvestris L. Plantation in the Dry Subzone of Northern Kazakhstan Steppes - Zalesov, S. V.; Dancheva, A. V.; Ayan, S.; Suyundikov, Z. O.; Rachimzhanov, A. N.; Razhanov, M. R.; Opletaev, A. S. (Kastamonu University, 2020)
Aim of study: Thinning efficiency after 18 years of cutting at the Scots pine (Pinus sylvestris L.) plantations, in the subzone of the dry grass steppe, were examined. Area of study: On 45-year-old Scots pine plantations on the territory of the state enterprise "ZhasylAimak" in Nur-Sultan city in the Northern Kazakhstan. Material and methods: The plantations were established by high density planting (13,300 seedlings/ha) of 2-year old seedlings. The planting was carried out on forest-suitable soils. To assess the silvicultural efficiency of the thinning in the plantation, the coefficient of growth tension or a complex estimated figure (CEF) was used. Main results: The research confirm that Scots pine plantations can be established in the subzone of dry fescue feather-grass steppe (Festuca valesiaca-Stipetum capillatae Sillinger 1930). The maximum silvicultural effect of thinning was achieved with three steps. In the 1st step of the thinning of the forest, 10-15 years old trees are cut down. Trees with over-developed crown are also cut down. The 2nd step is made in 25-30 years with thinning intensity of 25% by stock. The 3rd step is made in 40-50 years in a uniform way. Highlights: In the harsh climatic conditions of Northern Kazakhstan steppe, deciduous trees and shrubs begin to age and die much earlier than the long-lived Scots pine.
Keywords: THINNING; Pinus sylvestris; Plantation; Thinning; Forest productivity; Steppe; FOREST PRODUCTIVITY; Sarıçam; Plantasyon; Aralama; Orman verimliliği; Step; STEPPE; PLANTATION; PINUS SYLVESTRIS; 2. Zero hunger; 15. Life on land